Prevalence and risk factors for HIV, syphilis, hepatitis B, hepatitis C, and HTLV-I/II infection in low-income postpartum and pregnant women in Greater Metropolitan Vitória, Espírito Santo State, Brazil Prevalência e fatores de risco para a infecção por HIV, sífilis, hepatite B, hepatite C e HTLV-I/II em parturientes e gestantes de baixa renda atendidas na Região Metropolitana de Vitória, Espírito Santo, Brasil - Lucia Helena Mello de Lima; Maria Carmen Viana (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
Sexually transmitted infections during pregnancy pose a major risk to the fetus due to vertical transmission. The study's objective was to determine the prevalence of HIV, syphilis, hepatitis B and C, and HTLV-I/II infection among low-income postpartum and pregnant women treated in Greater Metropolitan Vitória, Espírito Santo State, Brazil, and the risk factors associated with these infections. A cross-sectional study was conducted from February to October 1999 assessing postpartum and pregnant women from the maternity ward of the Vitória Mercy Hospital and the Carapina Outpatient Referral Unit in the Municipality of Serra, respectively. Patients were systematically interviewed and had blood samples drawn for serological tests (HIV 1&2, VDRL, HbsAg, anti-HCV, and HTLV-I/II). A total of 534 patients (332 postpartum and 202 pregnant women) were assessed. Seroprevalence rates for the target infections in postpartum and pregnant women and the overall sample were as follows, respectively: HIV 0.9%, 0%, and 0.6%; syphilis 2.1%, 3.6%, and 2.7%; HBV 1.2%, 1%, and 1.1%; HCV 1.8%, 0.6%, and 1.4%; and HTLV-I/II 1.7%, 0.6%, and 1.3%. Factors associated with the various infections are presented and analyzed in light of other research findings from the literature. A ocorrência de doenças sexualmente transmissíveis durante a gravidez representa risco aumentado de morbidade e mortalidade para o feto e neonato em virtude da transmissão vertical. O objetivo deste estudo foi identificar a prevalência da infecção por HIV, sífilis, hepatites B e C e por HTLV-I/II em parturientes e gestantes de baixa renda da Região Metropolitana de Vitória, Espírito Santo, Brasil, e avaliar fatores de risco associados a essas infecções. Foi realizado estudo de corte transversal de fevereiro a outubro de 1999, avaliando 534 pacientes (332 parturientes e 202 gestantes). Todas as participantes foram submetidas a entrevista semi-estruturada, após a qual foi coletada uma amostra de sangue para realização de testes sorológicos (HIV 1 e 2, VDRL, HbsAg, anti-HCV e HTLV-I/II). A soroprevalência das infecções estudadas entre as parturientes, as gestantes e no total da amostra foi, respectivamente: HIV 0,9%, 0% e 0,6%; sífilis 2,1%, 3,6% e 2,7%; HBV 1,2%, 1% e 1,1%; HCV 1,8%, 0,6% e 1,4% e HTV-I/II 1,7%, 0,6% e 1,3%. Os fatores associados às infecções avaliadas são descritos e analisados à luz de achados de outros investigadores.